Enhancing Parathyroid Gland Visualization Using a Near Infrared Fluorescence-Based Overlay Imaging System - McWade, Melanie A (J Am Coll Surg, 2019)
BACKGROUND: Misidentifying parathyroid glands (PGs) during thyroidectomies or parathyroidectomies, could significantly increase post-operative morbidity. Imaging systems based on near-infrared autofluorescence (NIRAF) detection can localize PGs with high accuracy. These devices however depict NIRAF images on remote display monitors, where images lack spatial context and comparability with actual surgical field-of-view (FOV). In this study, we designed an Overlay Tissue Imaging System (OTIS) that detects tissue NIRAF and back-projects the collected signal as a visible image directly onto the surgical FOV instead of a display monitor, and tested its ability for enhancing parathyroid visualization. STUDY DESIGN: The OTIS was first calibrated with a fluorescent ink grid and initially tested with parathyroid, thyroid and lymph node tissues ex vivo. For in vivo measurements, the surgeon’s opinion on tissue-of-interest was first ascertained. After the surgeon looked away, the OTIS back-projected visible green light directly onto the tissue-of-interest, only if the device detected relatively high NIRAF as observed in PGs. System accuracy was determined by correlating NIRAF projection with surgeon’s visual confirmation for in-situ PGs or histopathology report for excised PGs. RESULTS: OTIS yielded 100% accuracy when tested ex vivo with parathyroid, thyroid and lymph node specimens. Subsequently, the device was evaluated in 30 patients who underwent thyroidectomy and/or parathyroidectomy. 97% of exposed tissue-of-interest were visualized correctly as PGs by the OTIS without requiring display monitors or contrast agents. CONCLUSION: While OTIS holds novel potential for enhancing label-free parathyroid visualization directly within the surgical FOV, further device optimization is required for eventual clinical use.